Analysis the Influence of Trust in Supervisor as Mediation on Employees Job Performance in Batam City’s Manufacturing Sector - Yuli Indah Fajar Dini; Edward Cornelyanto; Muhammad Donal Mon (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study investigates the interplay between leadership styles, leader emotional intelligence, and trust in supervisors, focusing on their impact on individual job performance in Batam City's manufacturing sector. Structural equation modelling (SEM) was used in this study. The result of analysis shows that leader emotional intelligence exert a direct, significant, and positive influence on trust in supervisors. Additionally with trust in supervisors included as a mediator, transformational leadership demonstrate a positive influence on job performance. Although the results indicate that transactional leadership and leader emotional intelligence has no direct, significant and positive impact on job performance, trust in supervisors that was influenced by a leader's approach to leadership will empower and boost employee's morale, and indirectly have a positive influence on job performance. Overall, the research underscores the importance of cultivating the right style of leadership, emotional intelligence, and trust in supervisors relationships to foster better employee outcomes in the manufacturing industry.